IMPLEMENTATION OF LOCAL WISDOM “TRI KAYA PARISUDHA” IN TOUR GUIDING IN BALI - I Gusti Ngurah Agung Suprastayasa (JURNAL KEPARIWISATAAN, 2022)
This study aims to identify the application of the teachings of Tri Kaya Parisudha local wisdom in guiding tours in Bali. For this reason, the study was conducted using qualitative approach by collecting data through in-depth interviews to five senior tour guides, scholars in Balinese culture, Hindu Religion and philosophy, and Hindu religious figures in Bali. The data obtained through the interview were analyzed descriptively. The results showed that Tri Kaya Parisudha local wisdom should become the reference for tourist guide in handling their clients. It could be used as philosophy, ethic, as well as a base for service to the clients or guests. However, there are still a number of tour guides who do not apply the Tri Kaya Parisudha teaching in handling their clients. More studies on this topic would enrich the topic and research on how to implement it in real life situation would be useful for improving the quality of tour guide in Bali.